Deterministic and Stochastic Cellular Mechanisms Contributing to Carbon Monoxide Induced Ventricular Arrhythmias - Al-Owais, Moza M.; Steele, Derek S.; Holden, Arun V.; Benson, Alan P. (Frontiers in Pharmacology, 2021)
Chronic exposure to low levels of Carbon Monoxide is associated with an increased risk of cardiac arrhythmia. Microelectrode recordings from single isolated rat and guinea pig ventricular myocytes exposed to CO releasing molecule CORM-2 excited at 0.2/s show repolarisation changes that develop over hundreds of seconds: action potential prolongation by delayed repolarisation, EADs, multiple EADs and oscillations around the plateau, leading to irreversible repolarisation failure. The measured direct effects of CO on these cells, and ion channels expressed in mammalian systems showed decreases in the maximal T- and L-type Ca++. peak and late Na+, ultra-rapid delayed, delayed rectifier, and the inward rectifier K+ currents. Incorporation of these CO induced changes in maximal currents in ventricular cell models; Gattoni et al., 2016 (rat) and Luo and Rudy, 1994 (guinea-pig) and human endo-, mid-myo- and epi-cardial O’Hara-Rudy (2011) models, by changes in maximal ionic conductance reproduces these repolarisation abnormalities. Simulations of cell populations with Gaussian distributions of maximal conductance parameters predict a CO induced increase in APD variability. Incorporation of these predicted CO induced changes in human ventricular cell electrophysiology into ventricular tissue and wall models give changes in indices for the probability of the initiation of re-entrant arrhythmia.